Pengaruh Kadar Aspal Efektif dan Tebal Selimut Aspal Terhadap Proporsi Rongga pada Campuran Laston: Influence of Effective Asphalt Content and Film Thickness on Voids Proportion of Asphalt Concrete - Ratna Yuniarti; Made Mahendra; Hasyim Hasyim; Rohani Rohani; I A O Suwati Sideman (LPPM Universitas Mataram, 2023)
In the mixing process between asphalt and aggregate, absorption of asphalt by the aggregate occurs through the pores of the aggregate. The volume of asphalt not absorbed by the aggregate can be defined as effective asphalt content which determines the percentage of airspaces in the compacted mix. The proportion of voids formed in the mixture contributes to the durability of the mixture against temperature and climate conditions. This study aims to examine the effect of effective asphalt content and the asphalt film thickness on the voids proportion in asphalt mixture. Based on the analysis, it can be concluded that the particle size distribution of the aggregate affects the total surface area of the aggregate in the mixture and the pores of the aggregate affect the effective percent of asphalt content. Aggregate with a small grain size produced a larger total surface area of aggregate. Meanwhile the use of aggregate with small pores produced a higher effective percent of asphalt content. The higher the effective asphalt content and the asphalt film thickness, the larger the voids in mineral aggregate and the voids filled with bitumen. In contrast, the voids in the mixture decreases with increase the effective asphalt content and the asphalt film thickness. In all the voids proportions analyzed, the effective asphalt content and the asphalt film thickness have a very significant effect.